Anti-aging sheath material and outdoor charging pile cable
By adding antioxidants, nanosilica, isoamyl alcohol and hydrophobically modified spherical nanosilica into the cable sheath material of outdoor charging piles, the problem of fast aging speed of cable sheath material is solved, and significant improvement in aging resistance and extended service life are achieved.
Patent Information
- Application Number
- CN202411913365.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The sheathing material of outdoor new energy vehicle charging pile cables is easily affected by changes in sunlight and temperature due to exposure to outdoors, resulting in aging speed and shortening service life.
A sheath material that is resistant to aging is used, which consists of SEBS resin, polyurethane thermoplastic elastomer, maleic anhydride grafted EVA, isoamyl alcohol, hydrophobically modified spherical nanosilicon dioxide, antioxidants and nanotitanium dioxide. The free radical reaction is blocked and ultraviolet light is absorbed by the addition of antioxidants and nanosilicon dioxide. Isomalcohol and hydrophobically modified spherical nanosilicon dioxide are used to reduce the content of organic small molecules and shear stress and extend the aging resistance of the sheath material.
It significantly enhances the aging resistance of the sheath material, extends the service life of outdoor charging pile cables, and maintains excellent strength and aging resistance.
Smart Images

Figure CN119708745A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a new energy charging pile, and in particular to an aging-resistant sheath material and an outdoor charging pile cable. Background Art
[0002] With the popularity of new energy vehicles, the installation rate of new energy vehicle charging stations has also increased. In outdoor new energy vehicle charging stations, the cables of the charging piles are basically exposed outdoors, affected by sunlight and temperature changes, so the cable sheaths of the charging piles age quickly.
[0003] Current cable sheath materials include TPE, TPU, PVC and other materials. Anti-aging agents are added when preparing the cable sheath materials for charging piles to slow down the aging of the cable sheath materials of the charging piles by shielding the organic phase from ultraviolet light, absorbing and converting light energy, and blocking free radical conduction.
[0004] The applicant has found through research on the aging mechanism of organic materials that the small organic molecules in the cable sheath play a key role in the aging process of the cable sheath material.
[0005] On the one hand, this type of organic small molecule substance is brought in by the residues in the organic raw materials of the cable sheath material and the side reactions of the additives at high temperatures during the preparation process. On the other hand, it is produced by the aging and decomposition of the organic phase. This type of organic small molecule substance has a complex composition and will further react under light to produce free radicals that cause the sheath material to further age.
[0006] Therefore, if the presence of organic small molecule materials in the cable sheath material can be reduced, it will be possible to further improve the aging resistance of the existing aging-resistant cable sheath material and extend the service life of the outdoor charging pile cable. Summary of the invention
[0007] In order to extend the service life of an outdoor charging pile cable, an aging-resistant sheath material and an outdoor charging pile cable are provided.
[0008] The above first invention objective of the present invention is achieved through the following technical solutions: An aging-resistant sheath material comprises the following raw materials in parts by weight: SEBS resin 60-100 parts, 20-40 parts of polyurethane thermoplastic elastomer, Maleic anhydride grafted EVA 10-14 parts, 1.3-2.4 parts of isoamyl alcohol, 5-7.9 parts of hydrophobically modified spherical nano-silicon dioxide, 3.4-4.2 parts of antioxidant, 8.4 to 10.1 parts of nano titanium dioxide.
[0009] By adopting the above technical solution, the common basic process in the aging process of the sheath material is that small molecular organic matter reacts under the action of light and heat to generate free radicals, and the free radicals further undergo a chain reaction with the organic polymer molecular chain to generate free radicals and broken organic polymer molecular chains, thereby continuously reacting to gradually age the sheath material, wherein the small molecular organic matter is defined as the starting material A, "small molecular organic matter reacts under the action of light and heat to generate free radicals" is defined as reaction B, and "free radicals further undergo a chain reaction with the organic polymer molecular chain to generate free radicals and broken organic polymer molecular chains" is defined as reaction C, Antioxidants and nano-silicon dioxide are added to this application; Antioxidants block the further reaction between free radicals in the organic phase and polymer molecular chains, thus hindering sheath aging from the perspective of reducing reaction C; Nano-titanium dioxide can absorb ultraviolet light and convert it into heat energy for release, thereby preventing sheath aging from the perspective of reducing reaction B; in addition, isoamyl alcohol and hydrophobically modified spherical nano-silica are also added in the present application; The boiling point of isoamyl alcohol is compatible with the basic organic phase of the sheath material of the present application. The boiling point of isoamyl alcohol is 8-10° C. lower than the melting processing temperature of the basic organic phase. When isoamyl alcohol evaporates during the preparation process, it carries small molecular organic matter in the organic phase to migrate outward and volatilize and remove, thereby reducing the content of small molecular organic matter in the sheath material. However, although single isoamyl alcohol has a removal effect on small organic molecules in the basic organic phase, the shear stress is still large when the basic organic phase is melted, the removal efficiency is low, and the optimal removal result under the limit removal is still difficult to achieve a good effect. Therefore, hydrophobically modified spherical nano-silica is also added in the present application. After being added, the sheath material can be strengthened, and the shear stress when the basic organic phase is melted can be significantly reduced during the preparation of the sheath material, so that the bubbles formed by the isoamyl alcohol and the small organic molecules carried by the isoamyl alcohol can be quickly and smoothly migrated to the surface of the basic organic phase melt and broken; The combination of isoamyl alcohol and hydrophobically modified spherical nano-silica can effectively reduce the content of organic small molecules in the sheath material to a certain value, and significantly enhance the aging resistance of the sheath material. From the perspective of reducing the starting material A, the aging of the sheath material is hindered. The combination of the three makes the sheath material of the present application have significant aging resistance.
[0010] Optionally: the particle size of the hydrophobically modified spherical nano-silica is 80 to 100 nm.
[0011] By adopting the above technical solution, the reinforcing effect on the sheath material is better, and at the same time, the shear force reduction effect when the basic organic phase is melted is the best. The obtained sheath material has both excellent strength and aging resistance.
[0012] Optionally, the hydrophobically modified spherical nano-silica is obtained by modification of alkyl polyglycoside and alkyl siloxane.
[0013] By adopting the above technical scheme, when the alkyl siloxane reacts and combines with the surface of the spherical nano-silica during the modification process, the alkyl polyglycoside is mixed into the surface of the spherical nano-silica through the reaction of the hydroxyl group and the siloxane group, thereby enhancing the effect of the hydrophobic modified nano-silica on reducing the shear stress of the basic organic phase melt. At the same time, the ring of the alkyl polyglycoside can open the ring when reacting with free radicals and block the transmission of free radicals, thereby reducing the generation of free radicals during the production and use of the sheath material, thereby further improving the aging resistance of the sheath material.
[0014] Optional: Modification of spherical nano-silica The modification method is as follows: Alkyl polyglycoside and water are prepared into soaking liquid A, and spherical nano-silica is then added into the soaking liquid A for soaking treatment, and then alkyl siloxane is added, and after mixing, ultrasonic vibration treatment, filtration, drying and sieving are performed to obtain hydrophobically modified spherical nano-silica.
[0015] By adopting the above technical scheme, the spherical nano-silica is first immersed in an immersion solution A prepared by alkyl polysaccharide and water, so that the surface of the spherical nano-silica can be cleaned and activated, and the mixing rate of the alkyl polysaccharide in the modification process can be increased, thereby improving the aging resistance of the sheath material.
[0016] Optional: Alkyl polyglycoside is а1,2-monomannitol, аmethyl polyglycoside.
[0017] By adopting the above technical solution, when а1,2-monomannitol and аmethyl glycoside are used, the strength of the sheath material is better and the aging resistance is the best.
[0018] Optional: The alkyl siloxane is n-octyltriethoxysilane.
[0019] By adopting the above technical solution, when n-octyltriethoxysilane is used, the sheath material has better strength and best aging resistance.
[0020] Optionally, the antioxidant is a compound of antioxidant 1010 and antioxidant 168.
[0021] By adopting the above technical solution, the sheath material has better aging resistance when the antioxidant 1010 and the antioxidant 168 are compounded.
[0022] The above second invention objective of the present invention is achieved through the following technical solutions: A cable comprises a core, an insulating layer and a sheath layer, wherein the sheath layer is made of the above-mentioned sheath material.
[0023] By adopting the above technical solution, the sheath used in the cable of the present application has excellent aging resistance and effectively extends the service life of the outdoor charging pile cable.
[0024] In summary, this application has at least the following beneficial effects: 1. In this application, the combination of isoamyl alcohol and hydrophobically modified spherical nano-silica can effectively reduce the content of small organic molecules in the sheath material to a certain value, and combined with antioxidants and nano-titanium dioxide, the aging resistance of the sheath material is significantly enhanced; 2. The hydrophobically modified spherical nano-silica is modified by using alkyl siloxane and alkyl polyglycoside. The obtained hydrophobically modified spherical nano-silica not only has a better effect on reducing the shear stress when the basic organic phase is melted, but also can further improve the aging resistance of the sheath; 3. The sheath used in the cable of this application has excellent aging resistance and effectively extends the service life of the outdoor charging pile cable. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a cross-sectional view of the cable in Example 14.
[0026] Reference numerals: 1. Battery core; 2. Insulation layer; 3. Sheath layer. DETAILED DESCRIPTION
[0027] raw material: Spherical nano-silica is a product sold by Zhejiang Manli Nano Technology Co., Ltd. and comes in five specifications: 50nm, 80nm, 90nm, 100nm, and 150nm.
[0028] а1,2-monomannitol, аmethyl glycoside, CAS: 59571-75-4, is a commercially available industrial grade product.
[0029] Decyl glucoside, CAS: 54549-25-6, is a commercially available industrial grade product.
[0030] n-Octyltriethoxysilane and vinyltriethoxysilane are commercially available industrial grade products.
[0031] The SEBS resin is SEBS YH-503T from Baling Petrochemical.
[0032] The polyurethane thermoplastic elastomer is BASF 1185A 10FHF from Germany.
[0033] The maleic anhydride grafted EVA was French Arkema 9307Y.
[0034] Isoamyl alcohol is a commercially available industrial grade product.
[0035] The antioxidant 1010 and the antioxidant pore 168 are commercially available products.
[0036] Preparation Example 1 The invention discloses a hydrophobically modified spherical nano-silica with a particle size of 90 nm, which is obtained by modifying the spherical nano-silica with alkyl polyglycoside and alkyl siloxane.
[0037] The alkyl polyglycoside is а1,2-monomannitol, аmethyl glycoside.
[0038] The alkyl siloxane is n-octyltriethoxysilane.
[0039] The preparation method is as follows: The alkyl polysaccharide and water are mixed in a mass ratio of 1:30 to obtain a soaking solution A; Soak 10kg of 90nm spherical nano-silicon dioxide into 31kg of soaking liquid A, stir and let stand for 1h; Then 10 kg of alkyl siloxane was added, and after being mixed evenly, the mixture was treated with 40 kHz ultrasonic oscillation for 2 hours. After the treatment, it was filtered, dried, and sieved to obtain hydrophobically modified spherical nano-silica with a particle size of 90 nm.
[0040] Preparation Example 2 A hydrophobically modified spherical nano-silica, which is different from Preparation Example 1 in that the particle size of the spherical nano-silica used is 50 nm, and the final screening requirement is also 50 nm.
[0041] Preparation Example 3 A hydrophobically modified spherical nano-silica, which is different from Preparation Example 1 in that the particle size of the spherical nano-silica used is 80 nm, and the final screening requirement is also 80 nm.
[0042] Preparation Example 4 A hydrophobically modified spherical nano-silica, which is different from Preparation Example 1 in that the particle size of the spherical nano-silica used is 100 nm, and the final screening requirement is also 100 nm.
[0043] Preparation Example 5 A hydrophobically modified spherical nano-silica, which is different from Preparation Example 1 in that the particle size of the spherical nano-silica used is 150 nm, and the final screening requirement is also 150 nm.
[0044] Preparation Example 6 A hydrophobically modified spherical nano-silica, which is different from Preparation Example 1 in that the alkyl polysaccharide used is decyl glucoside.
[0045] Preparation Example 7 A hydrophobically modified spherical nano-silica, which is different from Preparation Example 1 in that the alkyl siloxane used is vinyl triethoxy silane.
[0046] Preparation Example 8 The invention discloses a hydrophobically modified spherical nano-silica with a particle size of 90 nm, which is obtained by modifying the spherical nano-silica with alkyl polyglycoside and alkyl siloxane.
[0047] The alkyl polyglycoside is а1,2-monomannitol, аmethyl glycoside.
[0048] The alkyl siloxane is n-octyltriethoxysilane.
[0049] The preparation method is as follows.
[0050] The alkyl polyglycoside, alkyl siloxane and water are mixed in a mass ratio of 1:10:30 to obtain an immersion solution A; Soak 10kg of 90nm spherical nano-silicon dioxide into 41kg of soaking liquid A, stir and let stand for 1h; The mixture was then treated with 40 kHz ultrasonic oscillation for 2 h. After the treatment, it was filtered, dried, and sieved to obtain hydrophobically modified spherical nano-silica with a particle size of 90 nm.
[0051] Preparation Example 9 The invention discloses a hydrophobically modified spherical nano-silica with a particle size of 90 nm, which is obtained by modifying the spherical nano-silica with alkyl siloxane.
[0052] The alkyl siloxane is n-octyltriethoxysilane.
[0053] The preparation method is as follows.
[0054] Soak 10kg of 90nm spherical nano-silicon dioxide in 31kg of water, stir and let stand for 1h; Then 10 kg of alkyl siloxane was added, and after being mixed evenly, the mixture was treated with 40 kHz ultrasonic oscillation for 2 hours. After the treatment, it was filtered, dried, and sieved to obtain hydrophobically modified spherical nano-silica with a particle size of 90 nm.
[0055] Example 1 The invention discloses an aging-resistant sheath material, whose raw materials are SEBS resin, polyurethane thermoplastic elastomer, maleic anhydride grafted EVA, isopentanol, hydrophobically modified spherical nano-silicon dioxide, antioxidant and nano-titanium dioxide.
[0056] The hydrophobically modified spherical nano-silica was prepared in Preparation Example 1.
[0057] The antioxidant is prepared by mixing A1 and A2 in a mass ratio of 1:0.62.
[0058] The specific preparation method is as follows: 80kg SEBS resin, 34kg polyurethane thermoplastic elastomer, 12.5kg maleic anhydride grafted EVA, 2.2kg isopentanol, 6.4kg hydrophobically modified spherical nano-silica, 3.9kg antioxidant and 9.4kg nano-silica are uniformly mixed to obtain raw materials; the mixed raw materials are added into a screw extruder for melt extrusion to obtain an aging-resistant sheath material, and the temperatures of the first stage, the second stage, the stripping zone, the melting zone and the extrusion zone are 130°C, 135°C, 155°C, 160°C and 152°C respectively.
[0059] Example 2 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 2.
[0060] Example 3 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 3.
[0061] Example 4 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 4.
[0062] Example 5 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 5.
[0063] Example 6 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 6.
[0064] Example 7 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 7.
[0065] Example 8 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 8.
[0066] Example 9 An aging-resistant sheath material, which is different from Example 1 in that the hydrophobically modified spherical nano-silica used is prepared in Preparation Example 9.
[0067] Example 10 An aging-resistant sheath material, which is different from Example 1 in that the antioxidant used is antioxidant 1010.
[0068] Embodiment 11 An aging-resistant sheath material, which is different from Example 1 in that the antioxidant used is antioxidant 168.
[0069] Example 12 A sheath material resistant to aging, which differs from Example 1 in that the amount of raw materials used is different. Specifically, the raw material is obtained by uniformly mixing 60kg SEBS resin, 20kg polyurethane thermoplastic elastomer, 10kg maleic anhydride grafted EVA, 1.3kg isopentanol, 5kg hydrophobically modified spherical nano-silica, 3.4kg antioxidant, and 8.4kg nano-silica.
[0070] Example 13 A sheath material with anti-aging properties, which differs from Example 1 in that the amount of raw materials used is different. Specifically, the raw material is obtained by uniformly mixing 100kg SEBS resin, 40kg polyurethane thermoplastic elastomer, 14kg maleic anhydride grafted EVA, 2.4kg isopentanol, 7.9kg hydrophobically modified spherical nano-silica, 4.2kg antioxidant, and 10.1kg nano-silica.
[0071] Comparative Example 1 A sheath material, which differs from Example 1 in that the amount of isoamyl alcohol used is 0.
[0072] Comparative Example 2 A sheath material, which differs from Example 1 in that the amount of hydrophobically modified spherical nano-silica is 0.
[0073] Comparative Example 3 A sheath material, which differs from Example 1 in that the hydrophobically modified spherical nano-silica is replaced by spherical nano-silica of equal mass.
[0074] Detection: The initial tensile strength and initial elongation at break of the sheath materials obtained in Examples 1 to 13 and Comparative Examples 1 to 3 were tested, and then the tensile strength after aging and the elongation at break after aging were tested after accelerated aging, and the final technical tensile strength retention rate and elongation at break retention rate were measured.
[0075] Tensile strength retention rate = (tensile strength after aging / initial tensile strength) × 100%.
[0076] Retention rate of elongation at break = (retention rate of elongation at break after aging / retention rate of initial elongation at break) × 100%.
[0077] The tensile strength test was carried out according to ASTM-D412.
[0078] The elongation at break test was carried out according to ASTM-D412.
[0079] Accelerated aging method: GB / T 14049-2008, Appendix C xenon lamp method.
[0080] The test results are shown in the following table.
[0081] Table 1. Test results of Examples 1 to 13 and Comparative Examples 1 to 3 Tensile strength / MPa Elongation at break / % Tensile strength retention Retention rate of elongation at break Example 1 17.05 220.19 88.7% 89.1% Example 2 16.85 204.60 82.3% 83.8% Example 3 16.91 211.16 85.3% 86.7% Example 4 17.00 219.46 87.4% 87.6% Example 5 17.07 215.65 84.7% 85.2% Example 6 16.89 217.46 86.5% 87.3% Example 7 16.93 218.94 87.6% 88.1% Example 8 16.79 215.35 82.6% 83.4% Example 9 16.39 214.49 80.9% 81.8% Example 10 17.00 219.22 85.6% 86.7% Embodiment 11 16.97 218.87 84.7% 85.1% Example 12 16.59 210.57 86.4% 87.2% Embodiment 13 16.88 210.85 87.2% 86.7% Comparative Example 1 16.54 204.38 64.7% 66.1% Comparative Example 2 16.82 210.51 71.3% 72.7% Comparative Example 3 16.90 212.73 73.2% 74.3% Combined with Table 1, it can be seen from the comparison between Example 1 and Comparative Examples 1 to 3 that In Example 1, while using antioxidants and nano-silica, isoamyl alcohol and the hydrophobically modified nano-spherical silica prepared in Preparation Example 1 are also added; In Comparative Example 1, while using antioxidant and nano-silica, only the hydrophobically modified nano-spherical silica prepared in Preparation Example 1 was added; In Comparative Example 2, only isoamyl alcohol was added while using antioxidant and nano-silicon dioxide; The difference between Comparative Example 3 and Example 1 is that the hydrophobically modified spherical nano-silica is replaced by an equal mass of hydrophobically modified spherical nano-silica; In the test results, the tensile strength and elongation at break of Example 1 are greater than those of Comparative Examples 1-3, and the tensile strength retention rate and elongation at break retention rate of Example 1 are significantly greater than those of Comparative Examples 1-3.
[0082] The common basic process in the aging process of the sheath material is that small molecular organic matter reacts under the action of light and heat to generate free radicals, and the free radicals further react with the organic polymer molecular chain to generate free radicals and broken organic polymer molecular chain, so that the sheath material gradually ages due to continuous reaction, wherein the small molecular organic matter is defined as the starting material A, "small molecular organic matter reacts under the action of light and heat to generate free radicals" is defined as reaction B, and "free radicals further react with the organic polymer molecular chain to generate free radicals and broken organic polymer molecular chain" is defined as reaction C. Antioxidants and nano-silica are added in Example 1 to hinder the aging of the sheath from the perspective of reducing reaction C and reducing reaction B, respectively; isopentanol and hydrophobically modified spherical The hydrophobically modified spherical nano-silica can enhance the sheath material and significantly reduce the shear stress of the basic organic phase when it is melted during the preparation of the sheath material. At the same time, the boiling point of isoamyl alcohol is compatible with the basic organic phase of the sheath material of the present application, and the boiling point of isoamyl alcohol is 8-10°C lower than the melting processing temperature of the basic organic phase. During the preparation process, when isoamyl alcohol evaporates, it carries small molecular organic matter in the organic phase to migrate outward and volatilize and remove. Under the synergistic effect of the hydrophobically modified spherical nano-silica, the content of small organic molecules in the sheath material can be effectively reduced to a certain value, and the aging resistance of the sheath material can be significantly enhanced. From the perspective of reducing the starting material A, the aging of the sheath material is hindered. Therefore, the combination of the three makes the sheath material of the present application have significant aging resistance.
[0083] By comparing Example 1 with Examples 2 to 5, it can be seen that the particle size of the hydrophobically modified spherical nano-silica used in Example 1 is 90 nm, the particle size of the hydrophobically modified spherical nano-silica used in Example 2 is 50 nm, the particle size of the hydrophobically modified spherical nano-silica used in Example 3 is 80 nm, the particle size of the hydrophobically modified spherical nano-silica used in Example 4 is 100 nm, and the particle size of the hydrophobically modified spherical nano-silica used in Example 5 is 150 nm. Among the test results, the tensile strength, elongation at break, tensile strength retention rate, and elongation at break of Example 1 are the best. The tensile strength, elongation at break, tensile strength retention rate, and elongation at break of Example 3 are better than those of Example 2, and the tensile strength, elongation at break, tensile strength retention rate, and elongation at break of Example 4 are better than those of Example 5.
[0084] Therefore, when the particle size of the hydrophobically modified spherical nano-silica in the present application is 80-100 nm, the reinforcing effect on the sheath material is better, and the shear force reduction effect when the basic organic phase is melted is the best. The obtained sheath material has both excellent strength and aging resistance.
[0085] By comparing Example 1 with Examples 8 to 9, it can be seen that when the hydrophobically modified spherical nano-silica is modified in Example 1, the alkyl polyglycoside and water are first prepared into a soaking liquid A, and then the spherical nano-silica is added to the soaking liquid A for soaking treatment, and then the alkyl siloxane is added, mixed, and then subjected to ultrasonic vibration treatment, filtration, drying, and sieving to obtain the hydrophobically modified spherical nano-silica; In Example 8, when the hydrophobically modified spherical nano-silica is modified, alkyl polyglycoside, water, and alkyl siloxane are first prepared into a soaking liquid A, and then the spherical nano-silica is added into the soaking liquid A, and then subjected to ultrasonic vibration treatment, filtration, drying, and sieving to obtain the hydrophobically modified spherical nano-silica; In Example 9, when the hydrophobically modified spherical nano-silica is modified, water and alkyl siloxane are first prepared into a soaking liquid A, and then the spherical nano-silica is added into the soaking liquid A, and then subjected to ultrasonic vibration treatment, filtration, drying, and sieving to obtain the hydrophobically modified spherical nano-silica; In the test results, the tensile strength, elongation at break, tensile strength retention rate and elongation at break of Example 1 are better than those of Examples 8 and 9, and the tensile strength, elongation at break, tensile strength retention rate and elongation at break of Example 8 are better than those of Example 9. Therefore, during the modification process of the hydrophobically modified spherical nanosilica, the alkyl polyglycoside is mixed into the surface of the spherical nanosilica through the reaction of hydroxyl groups with siloxane groups, thereby enhancing the effect of the hydrophobically modified nanosilica on reducing the shear stress of the basic organic phase melt. At the same time, the ring of the alkyl polyglycoside can open the ring by reacting with free radicals and blocking the transfer of free radicals, thereby reducing the generation of free radicals during the production and use of the sheath material, thereby further improving the aging resistance of the sheath material.
[0086] In addition, the spherical nano-silica is first immersed in an immersion solution A prepared by alkyl polysaccharide and water, which can clean and activate the surface of the spherical nano-silica and increase the mixing rate of the alkyl polysaccharide in the modification process, thereby improving the aging resistance of the sheath material.
[0087] By comparing Example 1 and Example 6, it can be seen that the alkyl polyglycoside used in the hydrophobically modified spherical nanosilica in Example 1 is а1,2-monomannitol, аmethyl glycoside, and the alkyl polyglycoside used in the hydrophobically modified spherical nanosilica in Example 5 is decyl glucoside. The tensile strength, elongation at break, tensile strength retention rate, and elongation at break of Example 1 are better than those of Example 6. Therefore, when а1,2-monomannitol, аmethyl glycoside is used in the present application, the strength of the sheath material is better and the aging resistance is the best.
[0088] By comparing Example 1 and Example 7, it can be seen that the alkyl siloxane used in the hydrophobically modified spherical nano-silica in Example 1 is n-octyltriethoxysilane, and the alkyl siloxane used in the hydrophobically modified spherical nano-silica in Example 5 is alkyl siloxane. The tensile strength, elongation at break, tensile strength retention rate, and elongation at break of Example 1 are better than those of Example 7. Therefore, when n-octyltriethoxysilane is used in the present application, the strength of the sheath material is better and the aging resistance is the best.
[0089] Comparing Example 1 with Examples 10-11, the antioxidant used in Example 1 is a compound of antioxidants 1010 and 168, the antioxidant used in Example 10 is antioxidant 1010, and the antioxidant used in Example 11 is antioxidant 168. In the test results, the tensile strength retention rate and elongation at break of Example 1 are better than those of Examples 10-11. Therefore, the aging resistance of the sheath material is better when antioxidants 1010 and 168 are compounded.
[0090] During the research process of this application, there are other better solutions, such as Examples 12 to 13. The tensile strength, elongation at break, tensile strength retention rate, and elongation at break of Examples 12 to 13 are similar to those of Example 1, and they also have excellent strength and aging resistance.
[0091] Therefore, when the mass ratio of the raw materials used in this application is controlled as SEBS resin: polyurethane thermoplastic elastomer: maleic anhydride grafted EVA: isoamyl alcohol: hydrophobically modified spherical nano-silica: antioxidant: nano-titanium dioxide = (60-100): (20-40): (10-14): (1.3-2.4): (5-7.9): (3.4-4.2): (8.4-10.1), a sheath material with excellent strength and aging resistance can be obtained.
[0092] Embodiment 14 Combined with Figure 1 As shown, an outdoor charging pile cable includes a battery core 1, an insulating layer 2 and a sheath layer 3. The insulating layer 2 is coated on the outside of the battery core 1, and multiple strands of the battery core 1 wrapped with the insulating layer 2 are wrapped inside the sheath layer 3.
[0093] The sheath layer 3 is prepared from a sheath material, and the sheath material is one of the examples 1-13.
[0094] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as the modifications are within the scope of protection required by the present application, they shall be protected by the patent law.
Claims
1. An aging-resistant sheath material, characterized in that: Including the following raw materials by mass: SEBS resin 60~100 parts, Polyurethane thermoplastic elastomer 20~40 parts, Maleic anhydride grafted EVA 10~14 parts, 1.3~2.4 parts of isoamyl alcohol, 5-7.9 parts of hydrophobically modified spherical nano-silica, 3.4~4.2 parts of antioxidants, 8.4~10.1 parts of nano titanium dioxide.
2. The aging-resistant sheath material according to claim 1, characterized in that: The particle size of the hydrophobically modified spherical nano-silica is 80-100 nm.
3. The aging-resistant sheath material according to claim 1, characterized in that: The hydrophobically modified spherical nano-silica is obtained by modification of alkyl polyglycoside and alkyl siloxane.
4. The aging-resistant sheath material according to claim 3, characterized in that: The modification method of modified spherical nano-silica is as follows: Alkyl polyglycoside and water are prepared into soaking liquid A, and spherical nano-silica is then added into the soaking liquid A for soaking treatment, and then alkyl siloxane is added, and after mixing, ultrasonic vibration treatment, filtration, drying and sieving are performed to obtain hydrophobically modified spherical nano-silica.
5. The aging-resistant sheath material according to claim 3, characterized in that: The alkyl polyglycoside is а1,2-monomannitol, аmethyl glycoside.
6. The aging-resistant sheath material according to claim 3, characterized in that: The alkyl siloxane is n-octyltriethoxysilane.
7. The aging-resistant sheath material according to claim 1, characterized in that: The antioxidant is a compound of antioxidant 1010 and antioxidant 168.
8. A cable comprising a core (1), an insulating layer (2) and a sheath layer (3), characterized in that: The sheath layer (3) is made of the sheath material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Low VOC (volatile organic compound) polyformaldehyde (POM) material and preparation method thereof
CN104004317A
Crack-resistant halogen-free flame-retardant TPE charging pile cable material and preparation method thereof
CN108047629A
Halogen-free flame-retarding modified elastomer material as well as preparation method and application thereof
CN109486082A
TPU sheath material for charging cables as well as preparation and application of TPU sheath material
CN112375371A
Thermoplastic polyurethane elastomer for charging pile sheath and preparation method of thermoplastic polyurethane elastomer
CN114957967A